Promoting Professional Development for Teachers Through a Scale of Competence Assessment - Inmaculada García-Martínez; Miguel Pérez-Ferra; Jose Luis Ubago-Jiménez; Rocío Quijano-López (Research in Social Sciences and Technology, 2019)
Competencies are a key factor in the professional development of teachers. Additionally, Information and Communication Technologies (ICTs) in education are becoming increasingly important due to their potential in the field of education. The combination of both makes it easier to perform a comprehensive assessment of the level of competences of students in the Teacher Degree. The design of tasks and activities in order to promote their assessment enable classroom intervention. Indeed, this paper presents how ICTs have been used in university teaching. In order to respond to the evolution of training needs, we present a valid and reliable evaluation tool for professional competencies and learning results for prospective teachers (Pre-School and Primary Education). We applied for students from the Teacher Degree in their practicum period. Indeed, different learning and assessment tasks have been designed, some related to “correct” or “incorrect” teaching practices. This implies that the students have not only to do their tasks but to identify and to differentiate what is correct in their professional development. Finally, the instrument enables the assessment of the level of professional competencies acquired by prospective teachers during their training period.